Templat Tesis oleh Perpustakaan Universiti Sains Malaysia (Thesis Template by USM Library) - Basri, Jamilah Hassan; Muhammadan, Lizawati; Azmi, Noor Adilah (Perpustakaan Universiti Sains Malaysia, 2018)
Designed based on USM thesis guide, this thesis template by USM Library is now downloadable for you to edit, format, and export to suit your thesis requirements. It is a solution that will ease your thesis writing process as you do not have to worry too much on formatting your thesis draft. Note: Please click link on "Official URL" to download the template.